VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Computer Science and Match Analysis (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-127 Analysis of actions ended with shots at goal in Women`s European Football Championships P-128 Ulti-camera wide-angle video recording and analysis P-129 A critical survey of football rating systems P-130 Has soccer changed in the last three world championships? P-131 Movement analysis of elite junior Australian Rules Football: Comparison to elite senior results P-132 Kinematical analysis of Brazilian professional soccer players using an automatic tracking P-133 Offensive and defensive characteristics of 18th FIFA World Cup P-134 Home advantage in Turkish professional soccer P-135 Analysis of offensive playing patterns in soccer P-136 Techno-tactics and running distance analysis by camera P-137 Analysis of successful scoring situations in football matches P-138 Performance indicators distinguishing matches between regions in World Cup P-139 Regional comparisons of team performances in World Cup 2002 and 2006 P-140 Relevance of penalty kick methods and scoring ratio in World Cup 2006 P-141 Comparison of corner kicks of host and visitor teams in 2005-2006 Super League and 3rd League matches in Turkey P-142 Heart rate data files compiling for coaching control and research: HRDC Osasuna 1.0 P-143 Activity patterns in professional futsal players using global position tracking system P-144 Home advantage in Asian football leagues P-145 Heart-rate and activity-speed of professional soccer players in match